Effective Training Programs for Room Attendants in the Hospitality Industry - Wijoyo, Tuwuh Adhistyo; Alamsyah, Sandy; Intiar, Septa Intiar; Jabbar, Umar; Prabowo, Bayu Ade Prabowo (Journal of International Multidisciplinary Research, 2024)
This study examines the effectiveness of training programs for room attendants in the hospitality industry, focusing on their impact on performance, job satisfaction, and retention. Using a qualitative approach, in-depth interviews were conducted with 20 room attendants and 10 housekeeping managers across various hotel segments. The findings reveal that while initial training typically covers basic cleaning techniques and safety protocols, it often lacks depth in advanced methods and customer service skills. Challenges such as time constraints and reliance on informal learning are common, affecting the consistency and quality of training. Effective training programs were identified as those that provide comprehensive, ongoing instruction and incorporate innovative methods like virtual reality and gamified learning. The study also highlights the importance of mentorship programs and regular feedback to enhance training outcomes. Recommendations for improving training programs include developing detailed curricula, addressing time constraints, and adapting to emerging trends. By implementing these strategies, hotels can enhance room attendants' skills, satisfaction, and overall service quality, leading to improved guest experiences and operational success.